2021
DOI: 10.1038/s41598-021-01004-z
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-9 constitutes tight junctions of folliculo-stellate cells in the anterior pituitary gland

Abstract: The anterior pituitary gland regulates growth, metabolism, and reproduction by secreting hormones. Folliculo-stellate (FS) cells are non-endocrine cells located among hormone-producing cells in the anterior pituitary glands. They form follicular lumens, which are sealed by tight junctions (TJs). Although FS cells are hypothesized to contribute to fine-tuning of endocrine cells, little is known about the exact roles of FS cells. Here, we investigated the molecular composition of TJs in FS cells. We demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…First, the reactivity and specificity of the anti-CLDN9 mAb were tested against the C-terminal cytoplasmic region of human CLDN9 (Fig. 1A), which was recently established by our group (21). To this end, 293T cells were transiently transfected with individual CLDN expression vectors, followed by western blot and immunohistochemistry using whole-cell extracts and cell blocks, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the reactivity and specificity of the anti-CLDN9 mAb were tested against the C-terminal cytoplasmic region of human CLDN9 (Fig. 1A), which was recently established by our group (21). To this end, 293T cells were transiently transfected with individual CLDN expression vectors, followed by western blot and immunohistochemistry using whole-cell extracts and cell blocks, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, it was demonstrated that high CLDN9 expression predicts poor prognosis in patients with endometrial cancer using a newly established specific monoclonal antibody (mAb) (21). In addition, it was indicated that the combination of CLDN9 and CLDN6 is beneficial for predicting poor outcome in endometrial cancer.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…For this exclusion, in future studies, perhaps another specific marker for FSC should be used, or a panel of markers that would make the marking more specific. These could include, among others, Claudin-9, a marker of tight junctions of FSC [37] , Aldolase C [38] or IL-6 itself, which is stimulated by Adenosine, produced by FSC [39,40] .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Higashi et al . reported that claudin-9 is specifically expressed in S100β-positive cells [ 21 ]. However, whether tight junction-related proteins exist in the pituitary stem/progenitor cell niches remains unclear.…”
mentioning
confidence: 99%